Ch 312

#$&*

course Mth 158

10/27/11 at 3:30 p.m.

If your solution to stated problem does not match the given solution, you should self-critique per instructions at http://vhcc2.vhcc.edu/dsmith/geninfo/labrynth_created_fall_05/levl1_22/levl2_81/file3_259.htm.Your solution, attempt at solution:

If you are unable to attempt a solution, give a phrase-by-phrase interpretation of the problem along with a statement of what you do or do not understand about it. This response should be given, based on the work you did in completing the assignment, before you look at the given solution.

022. `* 22

*********************************************

Question: * 3.1.20 (was 3.1.6) (-2,5),(-1,3),(3,7),(4,12)}Is the given relation a function? Why or why not? If so what are its domain and range?

The set (-2,5),(-1,3),(3,7),(4,12) is a function.

The set of numbers is a function because every number in the domain corresponds to one exact number in the range.

The domain = {-2,-1,3,4}

The range = {5,3,7,12}

This relation is a function because every first element is paired with just one second element--there are no distinct ordered pairs with the same first element.

the domain is ( -2,-1,3,4)

the range is ( 5,3,7,12)

Another way of saying that this is a function is that every element of the domain appears only once in the relation.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating:

*********************************************

Question: * 3.1.46 / 34 (was 3.1.20) f(0), f(1), f(-1), f(-x), -f(x), f(x+1), f(2x), f(x+h) for 1 - 1 / (x+1)^2What are you expressions for f(0), f(1), f(-1), f(-x), -f(x), f(x+1), f(2x), f(x+h)?* 3.1.30. y = (3x-1)/(x+2)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Equation 3.1.46

f(0) = 1 - 1 / (0+1)^2

f(0) = 1 - 1/1

f(0) = 0

f(1) = 1 - 1 / (1+1)^2

f(1) = 1 - 1 / 4

f(1) = 3/4

f(-1) = 1 - 1 / (-1+1)^2

f(-1) = 1 - 1 / 0

f(-1) = 1

f(-x) = 1 - 1 / (-x+1)^2

f(-x) = 1 - 1 / (x^2 - 2x + 1)

-f(x) = - (1 - 1 / (x + 1)^2)

-f(x) = - (1 - 1 / (x^2 + 2x + 1))

-f(x) = 1 + 1 / (x^2 + 2x + 1)

f(x + 1) = 1 - 1 / ((x + 1) + 1)^2

f(x + 1) = 1 - 1 / (x + 2)^2

f(x + 1) = 1 - 1 / (x^2 + 4x + 4)

f(2x) = 1 - 1 / (2x + 1)^2

f(2x) = 1 - 1 / (4x^2 + 4x + 1)

f(x + h) = 1 - 1 / (x + h + 1)^2

f(x + h) = 1 - 1 / (x^2 + h^2 + 2x + 2h + 2hx + 1)

Equation 3.1.30

f(0) = (3(0) - 1) / (0+ 2)

f(0) = -1 / 2

f(1) = (3(1) - 1) / (1 + 2)

f(1) = 2/3

f(-1) = (3(-1) - 1) / (-1 + 2)

f(-1) = -4 / 1

f(-1) = -4

f(-x) = (3(-x) - 1) / (-x + 2)

f(-x) = (-3x - 1) / (-x + 2)

-f(x) = -(3(x) - 1) / (x + 2)

-f(x) = -(3x - 1) / (x + 2)

f(x + 1) = (3(x + 1) - 1) / (x + 3)

f(x + 1) = (3x + 2) / (x + 3)

f(2x) = (3(2x) - 1) / (2x + 2)

f(2x) = (6x - 1) / (2x + 2)

F(x + h) = (3(x+h) - 1) / (x + h + 2)

F(x + h) = (3x + 3h -1) / (x + h + 2)

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * STUDENT SOLUTION WITH INSTRUCTOR COMMENTS: f(x) = 1- 1/(x+2)^2

f(0) = 1- 1/ (0+2)^2

f(0) = 1-1/4

f(0) = 3/4

f(1) = 1- 1/ (3)^2

f(1) = 1- 1/9

f(1) = 8/9

f(-1) = 1- 1/(-1+2)^2

f(-1)= 1-1

f(-1)= 0

f(-x)= 1- 1/(-x+2)^2

f(-x)= 1 -1/ (x^2-4x+4)

-f(x) = -(1- 1/(x+2)^2)

-f(x)= -(1 - 1/ (x^2+4x+4))

-f(x) = -(1/(x^2 + 4x + 4)) - 1

** Your answer is right but you can leave it in factored form:

f(-x) = -(1 - 1/(x+2)^2)

= -1 + 1 / (x+2)^2. **

f(x+1) = 1- 1/((x+1) + 2)^2. This can be expanded as follows, but the expansion is not necessary at this point:

= 1- 1/ ((x+1)^2 +2(x+1) + 2(x+1)+4)

= 1- 1/ ((x+1)^2 +8x+8)

= 1- 1/ (x^2+2x+1+8x+8)

= 1- 1/(x^2 + 10x +9)

** Good algebra, and correct, but again no need to expand the square, though it is perfectly OK to do so. **

f(2x)= 1-1/(2x+2)^2

= 1- 1/(4x^2+8x+4)

** same comment **

f(x+h)= 1- 1/((x+h)+2)^2

= 1- 1/((x+h)^2 + 4(x+h) + 4)

= 1- 1/ (x^2 + 2xh + h^2+4x+4h+4)

** same comment **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): the equation that I was given in the question was

1 - 1 / (x+1)^2. The equation that was worked in the Given Solution was 1 - 1 / (x+2)^2. I think something is not right about the question that I was given. I see that I gave to much information.

------------------------------------------------

Self-critique Rating:

@& Your solution looks good in any case.*@

*********************************************

Question: * 3.1.36 / 44 (was 3.1.30)

Is y = (3x-1)/(x+2) the equation of a function?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

y = (3x-1)/(x+2) Is a function because for every value that you substitute in for x there is only one y value.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

** This is a function. Any value of x will give you one single value of y, and all real numbers x except -2 are in the domain. So for all x in the domain this is a function. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating:

*********************************************

Question: * 3.1.54 (was 3.1.40). G(x) = (x+4)/(x^3-4x)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

G(x) = (x + 4) / (x^3 - 4x) is a function.

The domain is {x| x does not = 0}

confidence rating #$&*: 1

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Starting with

g(x) = (x+4) / (x^3-4x) we factor x out of the denominator to get

g(x)= (x+4) / (x (x^2-4)) then we factor x^2 - 4 to get

g(x) = (x+4) / (x(x-2)(x+2)).

The denominator is zero when x = 0, 2 or -2.

The domain is therefore all real numbers such that x does not equal {0,2,-2}. **

STUDENT QUESTION:

Well, I went about it the long way and plugged in the numbers until I found what would make the denominator 0. I still have trouble factoring. I don’t see how factoring x out of the denominator helped to come up with the solution. Wouldn’t you still have to guess at x?

INSTRUCTOR RESPONSE

Once you've factored out x, the other factor is x^2 - 4. This is the difference of two squares and factors accordingly as (x-2) (x+2).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): I may have been supposed to know what to do with the equation. But I was given no instruction in the question of what to do. I see that I need to look at the equation in the text book also.

------------------------------------------------

Self-critique Rating:

@& It is assumed you have worked through the text problems and have your solutions handy when you complete this document.*@

*********************************************

Question: * 3.2.12 (was 3.1.50). Pos incr exp fnDoes the given graph depict a function? Explain how you determined whether or not the graph depicts a function.If the graph does depict a function then what are the domain and range of this function?

The graph does depict a function. I found this by using the vertical-line test.

The domain = {any real numbers}

The range = {any positive real number}

using the vertical line test we determine this is a function, since any given vertical line intersects the graph in exactly one point.

The function extends all the way to the right and to the left, and there are no breaks, so the domain consists of all real numbers.

The range consists of all possible y values. The function takes all y values greater than zero so the range is {y | y>0}, expressed in interval notation as (0, infinity).

The y intercept is (0,1); there is no x intercept but the negative x axis is an asymptote.

This graph has no symmetery.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating:

*********************************************

Question: * 3.2.16 (was 3.1.54) Circle rad 2 about origin.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Problem 3.2.16 is not a function.

confidence rating #$&*: 1

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Using the vertical line test we see that every vertical line lying between x = -2 and x = 2, not inclusive of x = -2 and x =2, intersects the graph in two points. So this is not a function

STUDENT COMMENT

I made the mistake by including the x intercepts, when the vertical line test is only the y intercepts and it has only 2

points.

INSTRUCTOR RESPONSE

You don't necessarily have to use the y intercepts. Any x value between -2 and 2, not including -2 or 2, defines a vertical line which intecepts the circle at two points.

That is, for -2 < x < 2, the vertical line through (x, 0) passes through the circle at two points.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating:

*********************************************

Question: * 3.2.22 (was 3.1.60). Downward hyperbola vertex (1,2 5).Does the given graph depict a function? Explain how you determined whether or not the graph depicts a function.If the graph does depict a function then what are the domain and range of this function?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

The graph does depict a line. I found this by using the vertical line test.

The domain = {x| x >= -3}

The range = {y| y >= 0}

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

Every vertical line intersects the graph at exacty one point so the graph depicts a function.

The function extends to the right and to the left without breaks so the domain consists of all real numbers.

The range consists of all possible y values.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): I was looking at the rang graph.

------------------------------------------------

Self-critique Rating:

*********************************************

Question: * 3.1.84 / 82 (was 3.1.70). f(x) =(2x - B) / (3x + 4).

If f(0) = 2 then what is the value of B?

If f(2)=1/2 what is value of B?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

(2(0) - B) / (3(0) + 4) = 2

-B / 4 = 2

-B = 2(4)

B = -8

(2(2) - B) / (3(2) + 4) = 1/2

(4 - B) / (10) = ½

4 - B = ½(10)

4 - B = 5

- B = 1

B = -1

confidence rating #$&*: 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

If f(0) = 2 then we have

2 = (2 * 0 - B) / (3 * 0 + 4) = -B / 4, so that

B = -4 * 2 = -8.

If f(2) = 1/2 then we have

1/2 = ((2*2)-B) / ((3*2)+4)

1/2 = (4-B) / 10

5 = 4-B

1=-B

B=-1

**

STUDENT COMMENT

I tried to write it on paper and follow how it was solved, but it is still a little confusing to me. Especially the second

part where f(2) = ½ I don’t see where you plug in the ½ or where you plug in the 2?

INSTRUCTOR RESPONSE

f(x) = (2x - B) / (3x + 4), so

f(2) = (2 * 2 - B) / (3 * 2 + 4) = (4 - B) / 10.

Since f(2) = (4 - B) / 10,

f(2) = 1/2 means

(4 - B) / 10 = 1/2.

We solve this equation for B, as in the given solution.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating:

*********************************************

Question: * 3.1.94 / 90 (was 3.1.80). H(x) = 20 - 13 x^2 (falling rock on Jupiter)What are the heights of the rock at 1, 1.1, 1.2 seconds?

When is the rock at each altitude: 15 m, 10 m, 5 m.When does the rock strike the ground?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

H(1) = 20 - 13(1)^2

20 - 13 = 7

The height of the rock would be 7 ft.

H(1.1) = 20 - 13(1.1)^2

20 - 13(1.21)

20 - 15.73 = 4.27

The height of the rock would be 4.27 ft.

H(1.2) = 20 - 13(1.2)^2

20 - 13(1.44)

20 - 18.72 = 1.28

15 = 20 - 13(x)^2

-5 = -13(x)^2

0.38 = x^2

x = 0.62

The rock is 15m off the ground after 0.62 sec.

10 = 20 - 13(x)^2

-10 = -13(x)^2

0.77 = x^2

x = 0.88

The rock is 10m off the ground after 0.88 sec.

5 = 20 - 13(x)^2

-15 = -13(x)^2

1.15 = x^2

x = 1.07

The rock is 5m off the ground after 1.07 sec.

0 = 20 - 13(x)^2

-20 = -13(x)^2

1.54 = x^2

x = 1.24

The rock would strike the ground after 1.24 sec.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

GOOD STUDENT SOLUTION: The height at t = 1 is

H(1) = 20-13

H(1) = 7m

The height at t = 1.1 is

H(1.1)= 20-13(1.1)^2

= 20-13(1.21)

= 20-15.73

H(1.1)= 4.27m.

The height at t = 1.2 is

H(1.2)= 20 - 13*(1.2)^2

= 20- 13 *(1.44)

= 20-18.72

H(1.2) = 1.28m.

The rock is at altitude 15 m when H(x) = 15:

15=20-13x^2

-5=-13x^2

5/13= x^2

x= +- .62

.62sec.

The rock is at altitude 10 m when H(x) = 10:

10=20-13x^2

-10=-13x^2

10/13 = x^2

x= +-.88

.88sec.

The rock is at 5 meter heigh when H(x) = 5:

5=20-13x^2

-15 = -13x^2

15/13=x^2

x= +- 1.07

1.07sec.

To find when the rock strikes the ground let y = 0 and we get

0= 20-13x^2. Adding -20 to both sides we have

-20=-13x^2. Multiplying both sides by -1/13 we get

20/13=x^2. Taking the square root of both sides we obtain the approximate value of x:

x=+-1.24

We conclude that

x = 1.24sec.

when the rock strikes the ground **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating:

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#This looks good. See my notes. Let me know if you have any questions. &#